Antioxidant Activity and Phytominerals Study of Some Asteraceae Species Growth in Western of Lraq - Ashwaq Talib Hameed1 , Nbaa Mutea Abid Al-alh2 , Asmaa Wajeh Jumaa2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
The antioxidant efficacy of aqueous extracts of twelve plants of the Asteraceae family, which is from naturalflora, was investigated by the method of scavenging free radicals of the compound Diphenylpicrylhydrazyl(DPPH) namely Aster subulatus, Calendula officinalis, Carduus pycnocephalus, Carthamus Oxantea, andCarthamus Oxantea. linearis, Launaea nudicaulis, Sonchus maritimus and Sonchus oleraceus, this activityis compared to an inhibition ratio (IC50) half of the maximum inhibitor concentration of 50 of the standardascorbic acid (vitamin C) antioxidant. the most effective of which was Carhamus oxyacantha, whichreached 68.430% and Centaurea pallescens 66.432%, and the lowest effectiveness in, Launaea nudicauliswas 40.430% and Koelpinia linearis was 43.816%. The mineral elements were analyzed in the aerial partof plants : (K, Na, , Mg, Ca, and P) using Atomic absorption (Spectrophotometer apparatus 5000 (Atomic) -the results showed that plants contain very good ratios of elements as the best plant in terms of content wasCarduus pycnocephalus and Carthamus oxykontha.